2016
DOI: 10.1007/s00227-016-2886-y
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and foraging habitats of Adélie and gentoo penguins in three different stages of their annual cycle

Abstract: new knowledge on the feeding ecology and foraging habitats of pygoscelid penguins. They confirm the importance of Antarctic krill during the annual cycle and improve the understanding of life strategies and predator-prey interactions essentially out of the reproductive period, in which the information is very limited. These results can help to establish new management strategies, particularly considering the potential overlap between predators and fisheries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 55 publications
2
31
1
2
Order By: Relevance
“…These findings are similar to those of Juáres et al (2016) at Stranger Point, King George Island, which suggested Adélie penguins had a greater variation in body feather δ 13 C values than gentoo penguins. These results also agree with tracking studies indicating that Adélie and chinstrap penguins disperse broadly during the post-breeding period while gentoo penguins remain close to their breeding colonies and forage in open-water, near-shore habitats (Wilson 2010;Hinke et al 2015).…”
Section: Comparison Of Foraging Strategies At King George Islandsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are similar to those of Juáres et al (2016) at Stranger Point, King George Island, which suggested Adélie penguins had a greater variation in body feather δ 13 C values than gentoo penguins. These results also agree with tracking studies indicating that Adélie and chinstrap penguins disperse broadly during the post-breeding period while gentoo penguins remain close to their breeding colonies and forage in open-water, near-shore habitats (Wilson 2010;Hinke et al 2015).…”
Section: Comparison Of Foraging Strategies At King George Islandsupporting
confidence: 91%
“…These results differ from those of Juáres et al (2016), which found no differences in the δ 15 N values of gentoo penguins between these two time periods at Stranger Point on King George Island, South Shetland Islands. The δ 13 C values and SEA b of gentoo penguins in our study indicated that foraging habitat use did not differ seasonally.…”
Section: Seasonal and Individual Variation At King George Islandcontrasting
confidence: 85%
See 3 more Smart Citations